Social media networking among university students at Szent István University - Csilla Czeglédi; Eszter Borsos; Erika Varga; Klara Veresné Valentinyi (Trendy v podnikání, 2019)
Over the last twenty years social media and networking have gained popularity and interest among the young, middle aged and elderly. It can be declared, however with caution, that it is the young who are connected to the social media the most. A current V4 no. 21820245 international research included a comprehensive focus group qualitative research on social media and trust building. Research was carried out in 6 focus groups at Szent István University, in Gödöllő and Budapest, Hungary, in October, 2019. The study provides an answer to the issues of why students use social media, how important they find self-presentation, networking and informationseeking in the social media, how fun it is for them, and what dangers they need to be aware of. Most of the answers were well expected by the researchers, however, some of them were contrary to the expectations.